Dawn of the Delphinidans: New Remains of Kentriodon from the Lower Miocene of Italy Shed Light on the Early Radiation of the Most Diverse Extant Cetacean Clade - Nobile, Francesco; Collareta, Alberto; Perenzin, Vittore; Fornaciari, Eliana; Giusberti, Luca; Bianucci, Giovanni (Biology, 2024)
Nowadays, the infraorder Delphinida consists of oceanic dolphins and porpoisesplus a handful of riverine and (sub-)Arctic forms. Overall, the delphinidans account for more thanhalf of the living cetacean species, thus comprising the core of present-day marine mammal diver-sity. The fossil record indicates that a critical phase of the evolutionary history of Delphinida oc-curred during the Early Miocene (c. 23.0–16.0 million years ago) when the extinct genus Kentriodonfirst appeared and became widespread worldwide. Our paper deals with a new delphinidan fossilfrom northeastern Italy, namely, an incomplete skull with ear bones dating back to 20.4–19.0 millionyears ago. This new specimen is recognized herein as a representative of Kentriodon and specificallyas the first unambiguous member of this genus from the Euro-Mediterranean region. Our new findrepresents the best candidate for being the most ancient member of Kentriodon. The evolutionarysuccess of Kentriodon (which lasted until the Late Miocene, less than 11.3 million years ago) mayhave been favored by the evolution of a peculiar biosonar system exploiting narrow-band high-frequency sounds, which in turn would have been hardly detectable by large-bodied, predatorytoothed whales. Furthermore, Kentriodon was seemingly characterized by a proportionally largerbrain compared to many coeval toothed whales, which in turn may evoke enhanced behavioral capabilities .